Teachers’ influence on the quality of pupils’ written explanations – Third-graders solving a simplified arithmagon task during a mathematics lesson - Laine, Anu; Ahtee, Maija; Näveri, Liisa; Pehkonen, Erkki; Hannula, Markku S (LUMAT: International Journal on Math, Science and Technology Education, 2018)
The aim of this study is to find out whether there is a connection between teacher’s request and guidance for written explanation and third-graders’ achievements in solving a non-standard problem. Pupils’ task was to solve a simplified arithmagon and to explain their solution. The lessons of seven teachers were recorded and their actions were examined and categorized during a problem-solving lesson. Also pupils’ solutions were checked and classified. The teacher’s behavior seems to have a crucial role in the quality of pupils’ written explanations. The third-graders had difficulties in writing their reasoning for solving the problem.